Physical Activity Is Associated with Weight Loss and Increased Cardiorespiratory Fitness in Severely Obese Men and Women Undergoing Lifestyle Treatment - Eivind Aadland; Lesley Robertson (Journal of Obesity)
We aimed to examine the relationship between physical activity (PA) and change in body weight and cardiorespiratory fitness (CRF) in severely obese men and women. Thirty-five subjects (10 men, body mass index 43.2±5.1 kg/m2) who participated in a 10-month lifestyle treatment programme were included. The PA duration correlated only with weight change for men (r=-0.69, P=.027 versus r=-0.19, P=.372 for women). Conversely, the PA intensity correlated only with CRF for women (r=0.61, P=.003 versus r=0.39, P=.340 for men). PA explained 55.8 and 5.6% of weight change for men and women, respectively, whereas the corresponding explained variances for CRF were 15.6 and 36.7%. We conclude that PA was associated with change in body weight and CRF; however, there was a trend towards a gender specific effect between severely obese men and women.